Contaminación por partículas de microplásticos en 5 especies de peces de interés comercial en la Amazonía Peruana - Da Cunha Najar, Stephany Daniela (2024)
Microplastic pollution is an emerging environmental issue in the aquatic ecosystems of the Peruvian Amazon. Establishing baseline information on the presence of these contaminants is essential for their regulation. This study investigated the presence, prevalence, and characteristics of microplastic particles in five commercially important fish species in Loreto, Peru. A total of 136 tissues (66 gills and 70 gastrointestinal tracts) from 68 specimens collected at major local markets were analyzed. The tissues underwent a microplastic extraction protocol using 10% sodium hydroxide (NaOH). The identification of microplastics was conducted visually with the aid of a wide spectrum stereoscope. A total of 1,497 microplastic particles were recorded, with a 100% prevalence across all species. Triporteus angulatus and Pseudoplatystoma punctifer exhibited the highest quantities of microplastics, with averages of 14.67 and 12.68 particles per individual, respectively. Among the analyzed tissues, gills showed the highest abundance of microplastics, with 961 particles compared to the gastrointestinal tract. The identified microplastics were predominantly blue in color, with 863 particles (62.95%), and elongated in shape, accounting for 1,441 particles (96.91%). A significant relationship was found between microplastic abundance and feeding habits, with omnivorous and carnivorous fish being the most affected. These findings suggest that microplastic pollution is widely distributed in the aquatic ecosystems of the Peruvian Amazon and that the ecological characteristics and feeding habits of the species influence microplastic load. The high prevalence of microplastics in commercially important species underscores the urgent need for regulatory measures.